UNDP Digital Leadership Learning Modules - and UNDP (United Nations Development Programme, 2022)
In order to support the digital transformation of government operations Digital Learning Modules for Civil Servants are available, an off-the-shelf package of capacity development in form of replicable training modules to empower public servants at both the local and central government level to be leaders of digital transformation for delivering better public services. The modules cover a multitude of fundamental areas: comprehending digital government and services, human-centered design for inclusivity and agile learning cycles; feature the importance of security and privacy, the value of data and how to manage data and technology related risks; spotlight the key role of supportive leadership and offer practical tools for assessing and overcoming main barriers to ensure a successful digital transformation journey.